Pharmacokinectical Study of Enrofloxacin in Sheep - A.K. Mohammed Ali, N.; J. Khamas, D.; A. Al-Khayyat, A. (The Iraqi Journal of Veterinary Medicine, 1990)
Enrofloxacin was injected subcutaneously to five sheep as a single dose of 5mg/kg b.w. Blood samples were collected periodically over 24 hours period and analysed by a microbiological method. Results indicated that the peak plasma concentration of 1.30 + 0.09 ug/ml was achieved two hours after the drug administration. The average biological elemination half-life from plasma was 2.42 + 0.27 hour, the apparent volume of distribution was 2.00 +0.18 1/kg and clearance of the drug was 9.80 + 0.61 ml/kg/min.